ANALISIS INFILTRASI PADA BERBAGAI TUTUPAN LAHAN DI SUB DAS BATI-BATI DAS MALUKA KALIMANTAN SELATAN - Yesi Eka Pratiwi; Syarifuddin Kadir; Badaruddin Badaruddin (Jurnal Sylva Scienteae, 2021)
Land cover can affect the physical properties of soil related to the pace, volume and capacity of infiltration on a land. The purpose of this research is to know the pace of infiltration and to analyze the large capacity and volume of infiltration on several different land cover in Sub DAS Bati-Bati DAS Maluka. Data collection required is primary data and secondary data. The research method is purposive sampling means the retrieval of infiltration data, laying of infiltrometer tools and soil sampling with the ring samples in the area that can be considered to represent all areas research. The pace of infiltration will be faster on land cover which is overgrown by vegetation such as plantation than only land cover of reeds and shrub. The highest infiltration pace is at a plantation of 84.86 mm, while the lowest in the reeds land cover is 74.67 mm. The infiltration pace is influenced by the physical properties of the soil, when the physical properties of the soil will also increase the infiltration pace. The infiltration capacity is directly proportional to the volume of infiltration, the highest value is on the land cover of the shrub with an average infiltration capacity of 198.1 mm/hr and volume infiltration 125.17 mm3. Lowest value in reeds land cover with average infiltration capacity of 157.58 mm/hr and volume infiltration 114.69 mm3. At Plantation land cover the average value of infiltration capacity is 185.88 mm/hr and the volume of infiltration is 121.58 mm3Tutupan lahan dapat memberikan pengaruh terhadap sifat fisik tanah yang berhubungan dengan laju, kapasitas dan volume infiltrasi pada suatu lahan. Tujuan dari penelitian ini ialah untuk mengetahui laju infiltrasi serta menganalisis besar volume dan kapasitas infiltrasi pada beberapa tutupan lahan yang berbeda di Sub DAS Bati-Bati DAS Maluka. Pengumpulan data yang diperlukan ialah data primer dan data sekunder. Metode penelitian dilakukan secara purposive sampling artinya pengambilan data infiltrasi, peletakan alat infiltrometer dan pengambilan sampel tanah dengan ring sample diarea yang dianggap dapat mewakili seluruh areal yang diteliti. Laju infiltrasi akan semakin cepat pada tutupan lahan yang banyak ditumbuhi oleh vegetasi seperti perkebunan daripada hanya tutupan lahan alang-alang dan semak belukar. Laju infiltrasi paling tinggi ialah pada perkebunan sebesar 84,86 mm, sedangkan paling rendah pada tutupan lahan alang-alang sebesar 74,67 mm. Laju infiltrasi dipengaruhi oleh sifat fisik tanah, saat sifat fisik tanah bagus maka laju infiltrasi juga semakin meningkat. Kapasitas infiltrasi berbanding lurus dengan volume infiltrasi, nilai tertinggi ialah pada tutupan lahan semak belukar dengan rata-rata kapasitas infiltrasi 198,1 mm/jam dan volume infiltrasi 125,17 mm3. Nilai terendah pada tutupan lahan alang-alang dengan rata-rata kapasitas infiltrasi 157,58 mm/jam dan volume infiltrasi 114,69 mm3. Pada tutupan lahan perkebunan nilai rata-rata kapasitas infiltrasi ialah 185,88 mm/jam dan volume infiltrasi sebesar 121,58 mm3.